Optimizing outcome reporting after radical cystectomy for organ-confined urothelial carcinoma of the bladder using oncological trifecta and pentafecta - Aziz, Atiqullah; Martini, Thomas (World journal of urology, 2015)
Abstract Radical cystectomy (RC) for urothelial carcinoma of the bladder (UCB) is associated with heterogeneous functional and oncological outcomes. The aim of this study was to generate trifecta and pentafecta criteria to optimize outcome reporting after RC.MethodsWe interviewed 50 experts to consider a virtual group of patients (age ≤ 75 years, ASA score ≤ 3) undergoing RC for a cT2 UCB and a final histology of ≤pT3pN0M0. A ranking was generated for the three and five criteria with the highest sum score. The criteria were applied to the Prospective Multicenter Radical Cystectomy Series 2011. Multivariable binary logistic regression analyses were used to evaluate the impact of clinical and histopathological parameters on meeting the top selected criteria.ResultsThe criteria with the highest sum score were negative soft tissue surgical margin, lymph node (LN) dissection of at least 16 LNs, no complications according to Clavien-Dindo grade 3-5 within 90 days after RC, treatment-free time between TUR-BT with detection of muscle-invasive UCB and RC <3 months and the absence of local UCB-recurrence in the pelvis ≤12 months. The first three criteria formed trifecta, and all five criteria pentafecta. A total of 334 patients qualified for final analysis, whereas 35.3 and 29 % met trifecta and pentafecta criteria, respectively. Multivariable analyses showed that the relative probability of meeting trifecta and pentafecta decreases with higher age (3.2 %, p = 0.043 and 3.3 %, p = 0.042) per year, respectively.ConclusionsTrifecta and pentafecta incorporate essential criteria in terms of outcome reporting and might be considered for the improvement of standardized quality assessment after RC for UCB.